1994
DOI: 10.1139/f94-307
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Eastern Oysters (Crassostrea virginica) Inhabiting the Laguna Madre, Texas, and Adjacent Bay Systems

Abstract: A survey of 16 enzyme systems and two structural proteins, among nine eastern oyster (Crassostrea virginica) populations in and adjacent to Laguna Madre, Texas, identified two genetically differentiated groups and the transition zone between them. The discontinuity in allele frequencies occurred between a reef in Corpus Christi Bay and reefs 26 km away in upper Laguna Madre. Although no fixed allelic differences were observed between populations from either side of the transition area, substantial frequency di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 5 publications
8
46
3
Order By: Relevance
“…Studying the population structure of oysters in Lagoons of Texas, King et al (1994) found significant differentiation with a mean F,, estimate of 0.164. The lagoons of Texas are up to 10 times older than those involved in the present study.…”
Section: Genetic Structure Of the Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the population structure of oysters in Lagoons of Texas, King et al (1994) found significant differentiation with a mean F,, estimate of 0.164. The lagoons of Texas are up to 10 times older than those involved in the present study.…”
Section: Genetic Structure Of the Populationsmentioning
confidence: 99%
“…In the Mediterranean only 2 bivalves (Ruditapes aureus and R, decussatus) from 1 lagoon (Etang d e Thau) have been analysed (Borsa & Thiriot-Quievreux 1990, Borsa et al 1991. Studying the genetic structure of oyster population of lagoons of southern Texas, USA, King et al (1994) found differentiation between lagoons, a result of importance for fishery and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in several marine species, estuaries and embayments, disconnected from ocean currents, retain local recruits, as evidenced by genetically distinct populations (e.g., King et al 1994;Beheregaray and Sunnucks 2001;Watts and Johnson 2004). Islands, especially archipelagos, which can disrupt and complicate the flow of currents (Scheltema 1986), are another potentially important source of barriers to connectivity, a possibility that was recognized by Darwin (1859, p. 401) in the Galapagos Islands.…”
mentioning
confidence: 99%
“…Genetic differentiation can be attributed to genetic drift and/or natural selection in populations isolated by hydrogeographic barriers (Hoover & Gaffney 2005), such as temperature, salinity and oceanic currents (Reeb & Avise 1990). King et al (1994) observed a distinct genetic composition in the Population genetics of mangrove oysters 7…”
Section: Discussionmentioning
confidence: 95%